Ewing sarcoma/primitive neuroectodermal tumor of the kidney treated with chemotherapy including ifosfamide. Issue 8 (21st June 2016) - Yoshihara, Hiroki; Kamiya, Takahiro; Hosoya, Yosuke; Hasegawa, Daisuke; Ogawa, Chitose; Asanuma, Hiroshi; Mizuno, Ryuichi; Hosoya, Ryota; Manabe, Atsushi
Abstract: Ewing sarcoma/primitive neuroectodermal tumor (ES/PNET) of the kidney is extremely rare, and is usually diagnosed after nephrectomy without neoadjuvant chemotherapy. Although ifosfamide and etoposide improve survival to a great extent in ES/PNET, the use of nephrotoxic agent, particularly ifosfamide, is a concern after nephrectomy. We describe the case of a 14‐year‐old female patient with abdominal mass who was diagnosed with ES/PNET of the right kidney after nephrectomy. Adjuvant chemotherapy including ifosfamide and etoposide were given. The estimated glomerular filtration rate decreased to 75% after the end of therapy. There was no evidence of recurrence 70 months after initial diagnosis.